Strategi Pengembangan Daya Tarik Wisata Budaya Kampung Adat Benteng None Di Desa Tetaf Kabupaten Timor Tengah Selatan Dalam Meningkatkan Kunjungan Wisatawan (Analisis Deskriptif Kualitatif) - Mirna Oematan, Juita L.D. Bessie, Abas Kasim (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2018)
Tourism is one of the important things for a country. With tourism, then a country,specificaly the local government where the tourism attraction is located, will getrevenue from each attractions income. One of the revenues source from tourism in TTSdistricts obtained from the cultural tourism interest traditon village of Benteng None.This research aims to identify the driving and inhibiting factors in thedevelopment of cultural tourism interest in Tradition Village of Benteng None. Also toknow the development strategy which needs to be done in order to increase visit toBenteng None. The sample in this research was 30 respondents who gained bypurposive sampling technic. The analysis tools used in this research is SWOT analysis.The results showed that by Matrix Grand Strategy in seen that cultural tourisminterest in Tradition Village of Benteng None are in quadrant I, which meanssupporting the strategy aggressively. The formulation the development strategies inBenteng None important to be noted from the various aspects such as tourists,transportation means, tourism interest, inftastructures and supporting facilities withinthe attraction, promotion, as well as need to be supported with funds and qualifiedhuman resources.Suggestions in this research is important to increase and improve the quality ofthe facilities in Benteng None, which still lacking; the cooperation with various relatedparties; the synergy between the Government whit the academics in the provision ofcompetent human resources in the field of tourism also improve the utilization ofinformation technology to introduce and promote potential tourism to the worldwide